Biochar-enriched compost and foliar application of banana stem sap on soil fertility, nutrient availability against Al3+ toxicity, and sweet corn yield in acidic soil - Islam, Mahammad Shariful; Khatun, Mst Fatima; Brahma, Shyamal; Kasim, Susilawati; Alam, Md Khairul (Taylor and Francis, 2025)
In tropical soils, inadequate nutrient availability, exacerbated by high concentrations of iron (Fe) and aluminum (Al) ions, significantly limits sweet corn yield by interfering with the nutrient uptake. This study tested the hypothesis that applying biochar-enriched compost (BEC), together with foliar application of banana stem sap (BSS), would enhance soil fertility and nutrient utilization compared to chemical fertilizers alone. Two consecutive pot experiments were conducted using four BEC levels (T1: control with 100% recommended chemical fertilizers; T2: 5 t/ha; T3: 10 t/ha; T4: 15 t/ha) and three BSS frequencies (F1: no spray; F2: two sprays; and F3: three sprays), arranged in a factorial randomized complete block design with three replications. Application of 15 t/ha BEC significantly improved soil properties, increasing pH by 1.79 units, potassium by 362%, calcium by 230%, magnesium by 253%, and cation exchange capacity by 80%, while reducing exchangeable Al3+ by 96% and soil acidity by 67%, compared to the control. Corn yield and biomass increased by 10.54% and 7.84%, respectively, with BEC and by 9.24% and 7.75% with the highest BSS frequency. In conclusion, the combination of 15 t/ha BEC and three foliar applications of BSS significantly improves sweet corn productivity and soil fertility in acidic soils.